Thermographic ocular temperature correlated with rectal temperature in cats. (December 2021) - Giannetto, C.; Di Pietro, S.; Falcone, A.; Pennisi, M.; Giudice, E.; Piccione, G.; Acri, G.
Abstract: Body temperature reflects the animal health and/or disease conditions. During clinical examination, temperature measurement is a basic step in veterinary medicine. The conventional method used is the rectal thermometry, particularly stressful in some subjects, especially for cats. A less stressful alternative method, such as infrared thermal imaging camera, is used in various fields of medicine for diagnosis, prognosis and correct therapeutic approaches. To evaluate the usefulness of infrared thermal imaging for the assessment of ocular temperature, twenty cats of different breeds (European, Siamese and Persian, 4–6 years old, mean body weight 4.3 ± 0.30 Kg) were enrolled in the study. In order to evaluate the applicability of the ocular temperature assessment through thermal imaging as a tool for measuring the animal's body temperature, the obtained values were compared with the rectal temperature values recorded in each cat by means of a digital thermo-camera. There were no differences between left and right eye; and a difference of about 1.19 °C between the ocular and rectal temperature value was recorded (p < 0.0001). Rectal and ocular temperatures were positively correlated (p < 0.0001; r = 0.93). In conclusion, we show that ocular temperature is an alternative method for body temperature measurement that can be used in clinical evaluation of cats, especially in cases where rectal temperature recording is not possible. Highlights: Infrared thermography can be a valid method for body temperature monitoring in cats. Surface temperature of right and left eyes were similar. Surface temperature of the eye was 1.2 °C less than rectal temperature.